(untitled) (Baghdad Science Journal, 2012)
This study included the preparation of the mixture aquatic extracts of Peganum harmala seeds and Pericarp of Punica granutum at concentration (10+50) ?(15+55)? (20+60) mgml .To study the influence of the mixture on the percentage of vitality of the protoscolices of E. granulosus In vitro, as the vitality of protoscolices had caused complete death when the using concentration at time 120,90,60 minute respectively. Also study the effect of mixture in white mice with infectious protoscolices In vivo and study the change occurred in the averages of the weights of the liver and spleen and the averages of its distension In vivo in processed group with mixture at concentration (15+55) , (10+50)mgml ,as which was approach to the negative group and the lowering significantly of these average occurred in processed groups with mixture and about of the positive group this study at appeared the possibility of using the mixture it a capability of the mixture which caused to the prohibition of the development of the protoscolices to the secondary hydatid cyst .